2006
DOI: 10.1080/00288306.2006.9515181
|View full text |Cite
|
Sign up to set email alerts
|

Reconnaissance sediment and microfossil analyses of a laminated short piston core from Lake Tekapo, South Island, New Zealand

Abstract: A 2.2 m piston core from the main basin of Lake Tekapo comprises millimetre-centimetre-scale alternations of light and dark laminae. Two much thicker layers occur near the base of the core and are interpreted as major slump deposits. Light laminae are predominantly fine silts with low microfossil concentrations. Dark laminae have higher clay, mica, and microfossil content and higher planktic/benthic diatom ratios. These findings are consistent with light laminae being deposited during times of high river flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…) and were interpreted as complex varves (Pickrill & Irwin, ) although the relation between seasonal climate, sedimentation processes and lake floor stratigraphy was not examined. Furthermore, problems with radiometric age control have hindered attempts to confirm whether the observed layers represent varves (Graham et al ., ; Mildenhall et al ., ). A robust understanding of the processes that control sedimentation is required to determine whether the sedimentary couplets in Lake Ohau accumulate annually and represent true varves.…”
Section: Introductionmentioning
confidence: 97%
“…) and were interpreted as complex varves (Pickrill & Irwin, ) although the relation between seasonal climate, sedimentation processes and lake floor stratigraphy was not examined. Furthermore, problems with radiometric age control have hindered attempts to confirm whether the observed layers represent varves (Graham et al ., ; Mildenhall et al ., ). A robust understanding of the processes that control sedimentation is required to determine whether the sedimentary couplets in Lake Ohau accumulate annually and represent true varves.…”
Section: Introductionmentioning
confidence: 97%
“…7C). Likewise inconsistency between diatom fossil distributions and lamina color was previously observed (Walker and Owen, 1999;Mildenhall et al, 2006). Unlaminated homogeneous sections contained the mixture of both benthic and planktonic diatoms, terrestrial plant particles, and mineral particles which were less observed in laminated sections.…”
Section: Laminae Observationmentioning
confidence: 73%
“…A number of these records are documented across the Northern Hemisphere (Mann et al 1998;, but there remains a need to develop high-resolution paleoclimate reconstructions from the Southern Hemisphere . New Zealand is one of only few landmasses that lie in the core of the climatically important Southern Hemisphere westerly wind belt but very few high-resolution terrestrial paleoclimate records have been recovered from the North and South Islands (Cook et al 2006Orpin et al 2010;Striewski et al 2013). Sediment cores collected from the distal end of Lake Ohau, South Island, New Zealand (Fig.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…1) and were interpreted as complex varves although the relation between seasonal climate, sedimentation processes and lake floor stratigraphy was not examined. Furthermore, problems with radiometric age control have hindered attempts to confirm whether the observed layers represent varves (Graham et al, 2005;Mildenhall et al, 2006). A robust understanding of the processes that control sedimentation is required to determine whether the sedimentary couplets in Lake Ohau accumulate annually and represent true varves.…”
Section: Introductionmentioning
confidence: 99%